Isolation, characterization, and complete genome analysis of P1312, a thermostable bacteriophage that infects Thermobifida fusca - Cheepudom, Jatuporn; Lee, Cheng-Cheng; Cai, Bingfu; Meng, Menghsiao (Frontiers in Microbiology, 2015)
Thermobifida fusca is a moderately thermophilic and cellulolytic actinobacterium. It is of particular interest due to its ability to not only produce a variety of biotechnologically relevant enzymes but also serve as an alternative host for metabolic engineering for the production of valuable chemicals from lignocellulosic agricultural wastes. No bacteriophage that infects T. fusca has been reported, despite its potential impacts on the utilization of T. fusca. In this study, an extremely thermostable bacteriophage P1312 that infects T. fusca was isolated from manure compost. Electron microscopy showed that P1312 has an icosahedral head and a long flexible non-contractile tail, a characteristic of the family Siphoviridae. P1312 has a double-stranded DNA genome of 60,284 bp with 93 potential ORFs. 31 ORFs encode proteins having putative biological functions. The genes involved in phage particle formation cluster together in a region of approximately 16 kb, followed by a segment containing genes presumably for DNA degradation/modification and cell wall disruption. The genes required for DNA replication and transcriptional control are dispersed within the rest of the genome. Phylogenetic analysis of large terminase subunit suggests that P1312 is a headful packaging phage containing a chromosome with circularly permuted direct terminal repeats.